Effect of aqueous extracts from the clove (Syzygium aromaticum) on chlorophyll content and breath in seedlings of cabbage (Brassica oleracea) - de Moura, Felipe Carlos; de Andrade, Heloísa Monteiro; Freitas, Darlielva do Rosário; Amaral, Camila Rodrigues (Eclética Química, 2015)
Some plants have characteristics of synthesizing secondary metabolic which influence on the growth and development of biological systems. Studies have been conducted in order to better understand the species of plants and chemicals with allelopathic activities, especially in agriculture. The objective of this paper is to analyze the influence of aqueous extracts of flower buds of the clove on the production of plant dry matter, content of chlorophyll a, b and total and potential respiratory activity of the roots of cabbage seedlings.